2016
DOI: 10.1007/978-3-319-29039-3_7
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Visualisation to Modelling-Based Teaching

Abstract: Both the creation of models and their communication to other people involve visualisations. These are, respectively, 'internal' (or mental) and 'external' (or public) representations, with the latter confusingly also being called visualisations. Perceptions by one of the five senses provide external representations. The modes of external representation of particular importance in science education are the: gestural, concrete, static visual (pictures, diagrams, graphs, mathematical and chemical equations), dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…As in previous research findings, the data above revealed that MERs played an important role in developing the mental model for atoms and molecules (Gilbert, 2005;Rapp, 2005). A form of learning progression was observed through the growing perception of molecular structure and their behaviour through students' experiencing the MERs, where their understanding level transitioned from the observable (macro) to the sub-micro level (Dickson et al, 2016;Gilbert et al, 2016;Gilbert et al, 2009;Meijer et al, 2013). This learning progression afforded the students the opportunity to cognitively delve more deeply.…”
Section: Multiple External Representations (Mers)supporting
confidence: 67%
See 1 more Smart Citation
“…As in previous research findings, the data above revealed that MERs played an important role in developing the mental model for atoms and molecules (Gilbert, 2005;Rapp, 2005). A form of learning progression was observed through the growing perception of molecular structure and their behaviour through students' experiencing the MERs, where their understanding level transitioned from the observable (macro) to the sub-micro level (Dickson et al, 2016;Gilbert et al, 2016;Gilbert et al, 2009;Meijer et al, 2013). This learning progression afforded the students the opportunity to cognitively delve more deeply.…”
Section: Multiple External Representations (Mers)supporting
confidence: 67%
“…Due to the ability to represent the complex phenomena of scientific concepts in multiple formats, it has been widely used in the science domain (Rau et al, 2015). In this regard, Johnstone (1993), Gilbert (2008) and Gilbert et al (2016) classified and discussed three representational levels in which the visualisation operates functionally, that is, at the macroscopic, sub-microscopic and symbolic levels (Johnstone, 1991). This study used these representational levels to facilitate students to understand the phenomena of abstract science concepts in the learning modules.…”
Section: Multiple External Representations (Mers)mentioning
confidence: 99%
“…Understanding the meaning of a symbol is not only knowing which object it represents, but also acknowledging its limitations in representing the object [3,9,30]. To enable communication using symbols, the meaning that is embedded in a symbol by its creator must be understood by all those who perceive it [1].…”
Section: Discussionmentioning
confidence: 99%
“…External representations are used by scientists to communicate with one another and with the non-scientist population. Therefore, the meaning that is embodied in a representation by its creator should be understood by all those who perceive it [1]. Furthermore, using external representations in a flexible manner allows scientists to manipulate those representations, thus creating a working model that can be updated when new experimental results are obtained or a new understanding is reached [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation